The progress principle : using small wins to ignite joy, engagement, and creativity at work - Amabile, Teresa; Kramer, Steven (Boston, Mass. : Harvard Business Review Press, 2011)
Explains how to foster progress, shows how to remove obstacles, including meaningless tasks and toxic relationships that disrupt employees' work lives, and offers advice on enhancing employees' inner work life.
Scenes from the organizational trenches -- The dynamics of inner work life -- The inner work life effect: how inner work life drives performance -- Discovering the progress principle -- The progress principle: the power of meaningful accomplishment -- The catalyst factor: the power of project support -- The nourishment factor: the power of interpersonal support -- At the end of the day -- Tending your own inner work life.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Employee motivation; Creative ability in business; Corporate culture; Motivation (Psychology); Creative ability; Corporate culture; Corporate culture; Creative ability in business; Employee motivation; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books